INTEGRATING POMEGRANATE PEEL WASTE-BASED LIP BALM PROJECTS INTO COLLOID CHEMISTRY LEARNING: A PROJECT-BASED APPROACH TO STUDENTS’ ENVIRONMENTAL LITERACY - Muazaroh, Kaffatiya Najmii; Rahmawati Sunarya, Risa; Sukmawardani, Yulia; Sari; Dahriah, Iis; Ali Nurdin, Muhammad; Sumawardani, Yulia (Lantanida Journal, 2026)
Senior high school students often face difficulties in translating environmental knowledge into concrete environmental behaviors, and organic waste like pomegranate peels remains underutilized in chemistry learning. This study aims to analyze students' environmental literacy through project-based worksheets (PjBL) using pomegranate peel waste for lip balm production in colloid chemistry. A pre-experimental one-shot case study involved 18 eleventh-grade students in Bandung, Indonesia. Selected through a purposive sampling technique. Data were collected using project-based worksheets, assessment rubics for student work and environmental literacy instruments. Results showed worksheet scores at 89.5 (very good). Environmental literacy scores were: environmental knowledge 81.2 (very good), cognitive skills 89.3 (very good), environmental attitude 82.0 (very good), and environmental behavior 79.3 (good). The findings indicate that PjBL-based activities supported students' engagement with contextual colloid chemistry concepts. However, the lower environmental behavior score (79.3) compared to other domains indicates a gap requiring further intervention. Overall, PjBL shows promise for developing environmental literacy by integrating chemistry learning with waste utilization.